New Dangers: Oral Manifestations Related to Smoking - Correa, Giovanna Cardoso; Versiane, Letícia Maria Santos; Assunção, Elida Lucia Ferreira; Lopes, Maria Carolina Soares; Bezerra, Ellen Aparecida Guimarães; Dos Santos, Thiago Alves Xavier; Pereira, Wilson Vicente Souza; Oliveira, Fabíola Belkiss Santos de; Bezerra Junior, Maximino Alencar (Revista Unimontes Científica, 2025)
Objective: To assess young people's perception of the impact of new forms of smoking on oral health. Methods: The present study is of the descriptive-quantitative type, where the primary research was used to obtain the data. Data collection took place in April 2022 with young people aged between 18 and 30 who live in the North of Minas Gerais. Results: The main results showed that young people are aware of the harmful effects of tobacco and marijuana but continue to use them. Conventional cigarettes were the most used by young people (36%), followed by electronic cigarettes (18%). Regarding oral manifestations, 54% of users reported a dry mouth sensation and 36% nicotine stains. Conclusion: It is concluded that young people are aware of the harmful effects of new forms of smoking. However, they continue to use it. New strategies for raising awareness of oral manifestations related to new forms of smoking are suggested, which may culminate in the cessation of the habit.